Eight newly recorded species of Ichneumonidae (Hymenoptera: Ichneumonoidea) from Iran - Kolarov, J.; Ghahari, H.; Jussila, R. (Federal Scientific Center of the East Asia Terrestrial Biodiversity, FEB RAS, 2025)
Eight species of the family Ichneumonidae (Hymenoptera) in the subfamilies Anomaloninae (one species), Banchinae (two species in two genera), Campopleginae (one species), Cryptinae (one species), Phygadeuontinae (two species in two genera), and Tryphoninae (one species) are recorded from Iran for the first time.